2008
DOI: 10.1002/anie.200803333
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Watson–Crick Base Pairing on a Solid Surface Studied at the Atomic Scale

Abstract: Surface Watson–Crick base pairing makes binary mixtures of the complementary nucleobases guanine (G) and cytosine (C) on Au(111) thermally stable up to the desorption temperature of the bases, whereas binary mixtures of the noncomplementary adenine (A) and cytosine segregate on heating (see STM images with DFT structures).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 37 publications
2
74
0
Order By: Relevance
“…It is reasonable to expect that higher efficiency and accuracy in the molecular recognition process exist between the biomimetically modified nucleobases compared to the nucleobases C and G alone, because fewer competitive hydrogen-bonded configurations are available for the modified nucleobases. This is indeed confirmed by our previous experiments [8] performed with the unmodified bases C and G, where we found that Watson-Crick G-C pairs were only randomly embedded into a C filament and characteristic fivefold ring structures without higher ordering. In summary, we have demonstrated that Watson-Crick hydrogen bonding can indeed play a vital role in driving natural molecular recognition between complementary nucleobases on a noble gold surface, even under well-controlled UHV conditions.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…It is reasonable to expect that higher efficiency and accuracy in the molecular recognition process exist between the biomimetically modified nucleobases compared to the nucleobases C and G alone, because fewer competitive hydrogen-bonded configurations are available for the modified nucleobases. This is indeed confirmed by our previous experiments [8] performed with the unmodified bases C and G, where we found that Watson-Crick G-C pairs were only randomly embedded into a C filament and characteristic fivefold ring structures without higher ordering. In summary, we have demonstrated that Watson-Crick hydrogen bonding can indeed play a vital role in driving natural molecular recognition between complementary nucleobases on a noble gold surface, even under well-controlled UHV conditions.…”
supporting
confidence: 88%
“…In support of this postulation, molecular recognition between complementary bases, most likely driven by hydrogen bonding alone, has already been observed both at the liquid/solid (HOPG) interface and on the noble Au(111) surface under extreme ultrahigh vacuum (UHV) conditions. [8][9][10] These previous experiments were, however, conducted with nucleobases alone, and hence did not take the presence of deoxyribose into account. It is therefore of utmost importance to explore the role that Watson-Crick hydrogen bonding plays at surfaces in chemical structures that mimic nucleotides so as to address the fundamental question of how the polymerization of nucleotides may have started in the prebiotic soup in the absence of enzymes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in many cases, e.g. for DNA bases 8,11,12,14,16 and melamine molecules on the Au(111) surface, 15,28 perylene-3,4,9,10-tetracarboxylic-3,4,9,10-dianhydride (PTCDA) molecules on the Ag(111) surface, 19,22,23 benzene 26 and PTCDA 30 molecules on the Au(111), Cu(111) and Ag(111) surfaces the calculated adsorption energies are too small (of the order of 0.1-0.2 eV) which is inconsistent with experimental observations of the desorption temperatures for these molecules (around 100-300 1C). This failure of standard generalized gradient approximation (GGA) functionals, such as e.g.…”
Section: Theoretical Background and Motivationmentioning
confidence: 99%
“…21,22 Molecular size and geometry, as well as interaction between molecules, are some of the key parameters determining whether or not molecular self-assembly is possible and what the final outcome will be. For instance, it has been shown that the mixture of adenine and cytosine, both DNA bases, does not lead to the formation of ordered multicomponent structures, 23 whereas several multicomponent structures have been obtained using semiconducting perylene-3,4,9,10-tetracarboxylic-3,4,9,10-dianhydride (PTCDA) molecules mixed pentacene 24 and 2,4,6-triamino-1,3,5-triazine, sym-triaminotriazine. 25 In this paper, we investigate the self-assembly of a nonsymmetric adenine DNA base ( Figure 1a) mixed with symmetric PTCDA molecules (Figure 1b) on a Au(111)-(22 Â √ 3) surface at room temperature in ultrahigh vacuum.…”
Section: ' Introductionmentioning
confidence: 99%